2017
DOI: 10.1002/dneu.22551
|View full text |Cite
|
Sign up to set email alerts
|

Erbin and ErbB2 play roles in the sexual differentiation of the song system nucleus HVC in bengalese finches (Lonchura Striata var. domestica)

Abstract: Song control nuclei have distinct sexual differences in songbirds. However, the mechanism that underlies the sexual differentiation of song nuclei is still not well understood. Using a combination of anatomical, pharmacological, genetic, and behavioral approaches, the present study investigated the role of erbb2 (a homolog of the avian erythroblastic leukemia viral oncogene homolog 2) and the erbb2-interacting gene, erbin, in the sexual differentiation of the song nucleus HVC in the Bengalese finch. We first f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
(114 reference statements)
1
7
0
Order By: Relevance
“…Our study and other reports indicate that the sexual differentiation of the HVC includes at least two processes, that is, cell proliferation in the VZ where HVC progenitors are produced and neural differentiation toward HVC neurons (Alvarez‐Buylla et al., 1994; Alvarez‐Buylla & Nottebohm, 1988; Burek et al., 1994; Chen et al., 2014; Zeng et al., 2007; Zhao et al., 2018). Estrogen, a brain‐derived neurotrophic factor, can partly masculinize the female HVC by changing the activities of the two processes (Arnold, 2003; Carruth et al., 2002; Chen et al., 2014; Hartog et al., 2009; Rasika et al., 1999).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Our study and other reports indicate that the sexual differentiation of the HVC includes at least two processes, that is, cell proliferation in the VZ where HVC progenitors are produced and neural differentiation toward HVC neurons (Alvarez‐Buylla et al., 1994; Alvarez‐Buylla & Nottebohm, 1988; Burek et al., 1994; Chen et al., 2014; Zeng et al., 2007; Zhao et al., 2018). Estrogen, a brain‐derived neurotrophic factor, can partly masculinize the female HVC by changing the activities of the two processes (Arnold, 2003; Carruth et al., 2002; Chen et al., 2014; Hartog et al., 2009; Rasika et al., 1999).…”
Section: Discussionsupporting
confidence: 67%
“…Our study examined the effect of Wnt, Bmp, and Notch signaling pathways on cell proliferation in the VZ overlying the developing HVC and on neural differentiation toward HVC neurons at PHD 15. Brain explants containing male or female HVC were taken using the same method used in our two previous reports (Chen et al., 2014; Zhao et al., 2018). Our results first indicated that β‐catenin in the Wnt signaling pathway was expressed in a sexually different way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more research is needed in adult animals to determine differences between age, size, and an animal’s ability to regenerate. Previous studies noted the pro‐survival effect of the Nrg1 pathway on nervous cells during neurodegenerative diseases and SCI (Zhang et al , ; ; Modol‐Caballero et al , ) as well as its effect on remyelination (Taveggia et al , ; Fricker et al , ) and stem cell proliferation and differentiation (Ghashghaei et al , ; Sato et al , ; Reeve et al , ; Zhao et al , ). This well‐documented role of Nrg1 in pro‐regenerative processes in the nervous system led us to suspect that it could contribute to spinal cord regeneration in the highly regenerative axolotl salamander.…”
Section: Discussionmentioning
confidence: 95%